Evaluation of Genotoxicity and Mutagenicity of Ketamine on Human Peripheral Blood Leukocytes and in Salmonella typhimurium. (February 2020) - Cavalcanti, Bruno Coêlho; de Andrade Neto, João Batista; de Sousa Silva, Antônio Adailson; Barreto, Francisco Stefânio; de Oliveira Ferreira, José Roberto; da Silva, Cecília Rocha; Aires do Nascimento, Francisca Bruna S.; do Amaral Valente Sá, Lívia Gurgel; Magalhães, Hemerson Iury Ferreira; Nobre Júnior, Hélio Vitoriano; de Moraes, Manoel Odorico
Abstract: Ketamine is a potent uncompetitive NMDA receptor antagonist that provides amnesia, analgesia, environmental dissociation and immobility, where it has its cytotoxic effect well described in the literature. However, the work on its genotoxic/mutagenic potentials are scarce and insufficient and does not allow a reasonable evaluation of its role. Thus, in the present work, we decided to evaluate the genotoxic and mutagenic effects of ketamine on human peripheral blood leukocytes (PBLs) and Salmonella typhimurium (TA98, TA97a, TA100, and TA102) through several well-established experimental protocols based on different parameters in the presence or not of exogenous metabolizing S9 fraction. Our data revealed that ketamine induces a weak cytotoxic effect on human PBLs after 24 h and is devoided of hemolytic effects. A small amount of DNA strand breaks levels were detected in the modified comet assay (employment of FPG enzyme) only at highest concentrations (500 and 700 μg/mL) of ketamine, highlighting our pro-oxidant data regarding ketamine. However, the oxidative DNA lesions were almost completely repaired which reflects in the lack of mutagenesis (micronuclei and chromosomal aberrations) on human PBLs and no increases in revertants numbers on S. typhimurium /microsome test (500 to 5000 μg/plate). In summary, ketamine is a weak oxidative DNA damaging agent and is devoid of mutagenic properties on eukaryotic and prokaryotic models. Highlights: Ketamine induces a weak cytotoxic effect on PBLs after 24 h. A small amount of DNA strand breaks levels were detected in the modified comet assay (employment of FPG enzyme). The oxidative DNA lesions were almost completely repaired which reflects in the lack of mutagenesis. No increases in revertants numbers on S. typhimurium /microsome test